Deformation monitoring using GNSS-R technology. Issue 10 (15th May 2019) - Yang, Yang; Zheng, Yu; Yu, Wenkun; Chen, Wu; Weng, Duojie
Abstract: GNSS reflectometry (GNSS-R) has been widely studied in recent years for various applications, such as soil moisture monitoring, biomass analysis, and sea state monitoring. This paper presents the concept of a novel application of using GNSS-R technology for deformation monitoring. Instead of installing GNSS on the deformation body to sense the movement, GNSS-R deformation monitoring system estimates the deformation from receiving GNSS signal reflected by the deformation body remotely. A prototype of GNSS-R deformation monitoring system has been developed based on GNSS software receiver technology. A 3D geometrical model of GNSS signal reflection has been used to reveal the relationship between the change of carrier phase difference and deformation. After compensating the propagation path delay changes caused by satellite movement, the changes in the remaining carrier phase difference are linked to the deformation. Field tests have been carried using the GNSS-R system developed and the results show sub-centimeter level deformation can be observed with the new technology. Unlike other GNSS deformation monitoring methods, GNSS-R receivers are not installed on the slope which makes this new technology more attractive.